Gold nanoparticle-based supramolecular approach for dye-sensitized H2-evolving photocathodes. Issue 41 (30th September 2022) - Lalaoui, Noémie; Abdellah, Mohamed; Materna, Kelly L.; Xu, Bo; Tian, Haining; Thapper, Anders; Sa, Jacinto; Hammarström, Leif; Ott, Sascha
Abstract : Light-induced hole injection from a NiO-bound molecular dye provides electrons that are channeled through gold nanoparticles to molecular catalysts for hydrogen evolution. Abstract : Solar conversion of water into the storable energy carrier H2 can be achieved through photoelectrochemical water splitting using light adsorbing anodes and cathodes bearing O2 and H2 evolving catalysts, respectively. Herein a novel photocathode nanohybrid system is reported. This photocathode consists of a dye-sensitized p-type nickel oxide (NiO) with a perylene-based chromophore (PCA ) and a tetra-adamantane modified cobaloxime reduction catalyst (Co ) that photo-reduces aqueous protons to H2 . An original supramolecular approach was employed, using β-cyclodextrin functionalized gold nanoparticles (β-CD-AuNPs ) to link the alkane chain of the PCA dye to the adamantane moieties of the cobaloxime catalyst (Co ). This new architecture was investigated by photoelectrochemical measurements and via femtosecond-transient absorption spectroscopy. The results show that irradiation of the complete NiO|PCA|β-CD-AuNPs|Co electrode leads to ultrafast hole injection into NiO (π = 3 ps) from the excited dye, followed by rapid reduction of the catalyst, and finally H2 evolution.